Physiological behavior of arabic coffee seedlings (Cv. obatá and catucaí) submitted to water deficit - Zuñiga, Enrique Alonso [UNESP]; Machuca, Luz Maria Ruiz [UNESP]; Dos Santos, Osvaldir Feliciano [UNESP]; de Souza, Mara Lúcia Cruz [UNESP]; de Oliveira, Dariane Priscila Franco [UNESP]; Broetto, Fernando [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2019)
In this work, biometric characteristics and pigment content were assessed in Arabica cv. Obatã and Catuaí cultivated under water deficit (WD). The experiment was conducted in an agricultural greenhouse from December to May, 2016-2017 in the district of Rubião Júnior (Department of Chemistry and Biochemistry of IB / UNESP), Botucatu-SP. Treatments were arranged in a randomized block design in a 3x2 factorial scheme in subdivided plots, with four replications per treatment. The treatments applied were: T1-100% of field capacity (FC)-C = Control, well irrigated plants, T2-50% of FC-MWD = moderate water deficit and T3-25% FC-SWD = severe water deficit. Plant height, leaf area and chlorophyll content (a and b) were assessed at 90, 120, 135 and 165 days after transplanting (DAT). It was verified that only plant height and leaf area decreased significantly as function of stress severity. Among the cultivars, only cv. Obatã presented better adaptation to the effects of WD.
Comportamento fisiológico de mudas de cafeeiro arábica (Cv. obatã e catucaí) submetidas à deficiência hídrica
Keywords: Biometry; Coffea arabica; Foliar pigments; Water deficit